Towards the Next Generation of the MITA Digital Platform for Transforming Agriculture in West and Central Africa - Zounon, Eunice Emmanuel; Kpadonou, G Esaie; Ganyo, Komla Kyky; Chaffaï, Laouali Chaïbou; Nadinga, Poko Alida; Segnon, Alcade Christel; Lamien, Nieyidouba; Zougmore, Robert Bellarmin (2025)
Since its creation in 2016 the MITA digital platform has shown its capacity in scaling agricultural technologies and innovations. Now, the platform needs to be upgraded to enhance the adoption and use aspect of the dissemination process. The MITA modernization process is user-driven, based on stakeholder experience and feedback got from the use of the platform after a comprehensive diagnostic study conducted to identify technical challenges embedded in the platform. Key enhancements include fixing malfunctions in user registration and communication processes, improving statistics tracking, integrating mobile/offline versions, and optimizing web performance and documentation of the platform. The Next Generation of MITA is expected to have a new data control and analytics system to better assess the platform’s reach, user engagement, and the adoption of technologies, supporting more evidence-based decision-making. From this process, expected outcomes include a more intuitive user experience, a fully functional mobile version, clearer communication channels, and regular stakeholder training to boost platform ownership and long-term use across West and Central Africa.